Mutu Minyak Jelantah Dengan Adsorben Biji Salak (Salacca zalacca (Gaertn.)Voss) menggunakan Parameter Bilangan Peroksida dan Asam Lemak Bebas: Quality of Used Cooking Oil With Snake Fruit (Salacca zalacca (Gaertn.) Voss) Seed Adsorbent Using Parameters of Peroxide Value and Free Fatty Acids - Ihwan Ihwan; Fadlia Fadlia; Syariful Anam (Universitas Tadulako, 2019)
Quality of used cooking oil with snake fruit (Salacca zalacca (Gaertn.) Voss) seed adsorbent has been conducted. This study aims to determine the ability of snake fruit seed in reducing peroxide value and free fatty acids in used cooking oil which can improve the quality and extend usage lifespan of the used cooking oil. The oil sampled in this study was packaged cooking oil which is usually used to fry food untill 7th frying. The oil was then neutralized using snake fruit activated charcoal. The test refers to the Indonesian National Standard (SNI) 7709: 2012 as the quality requirements of cooking oil. The results showed that snake fruit activated charcoal can reduce peroxide value as much as 56.18% and free fatty acid 76.04% in the used cooking oil.